1997
DOI: 10.1111/j.1747-6593.1997.tb00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Reliable Outputs of Groundwater Sources

Abstract: The described methodology for the assessment of the reliable outputs of groundwater sources was developed during a recent contract for UK Water Industry Research. It is relatively simple and flexible so that it can be applied to the wide range of groundwater source types and aquifers encountered in the UK. It can be used for all water level conditions, including that of drought, and for various demand conditions. There are two approaches, one based upon operational data and the second upon the analysis and ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the case of a new well, with no operational records, an analytical approach can be used to determine the potential yield and then the reliable yield. This method consists of the calculation of short-term drawdown, derived from pumping tests (for example, step-test data), extrapolation of longer-term pumping drawdown trend (for example, 200 days) and its conversion, taking into account the drought water level [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a new well, with no operational records, an analytical approach can be used to determine the potential yield and then the reliable yield. This method consists of the calculation of short-term drawdown, derived from pumping tests (for example, step-test data), extrapolation of longer-term pumping drawdown trend (for example, 200 days) and its conversion, taking into account the drought water level [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…This can occur in abstraction or reinjection wells, heat exchangers or pipelines. The regular documentation of well specific capacity (e.g., on Q/s diagrams [51][52][53]), and monitoring of pressure losses in pipelines, heat exchangers and reinjection mains is essential. 9.…”
mentioning
confidence: 99%
“…Published approaches to quantifying individual borehole yields in fractured rocks during drought periods are scant. Individual case studies have been reported in the USA (Hammond, 2018), UK (Beeson et al, 1997), South Africa (van Tonder et al, 2001), Italy (Piscopo and Summa, 2007) and…”
mentioning
confidence: 99%
“…The dearth of published methodologies for assessment of borehole yields during droughts means that this research builds on approaches reported in the UK. In the UK, borehole yields are estimated using the approach outlined by Beeson et al (1997) and Misstear and Beeson (2000) and shown in Figure 1. In brief, observed step-drawdown test data are used to derive the shape of a yield-…”
mentioning
confidence: 99%
See 1 more Smart Citation